Association between anterior alveolar dimensions and vertical facial pattern among Saudi adults - Adel M. Alhadlaq (Saudi Dental Journal)
Objective: To establish the anterior alveolar dimensions among a sample of Saudi subjects with different vertical facial heights. Materials and methods: Lateral cephalometric radiographs of 63 Saudi subjects (30 males and 33 females) were included in this retrospective study. The sample was divided into high angle (SN-MP ⩾ 39°), low angle (SN-MP ⩽ 28°) and average angle (30° < SN-MP < 37°) groups. The anteroposterior and vertical dimensions of the alveolus surrounding the root apex of upper and lower incisors were calculated. Results: The anterior alveolar dimensions exhibited significant differences (p < 0.05) between the different vertical facial height groups. The males and females demonstrated significant differences (p < 0.05) in the anterior alveolar dimensions for the same vertical jaw relationship. Conclusions: Both gender and the vertical jaw relationship can be factors for different height and thickness of the anterior alveolus. Clinicians must be aware of differences in the anterior alveolar dimensions for safe and sound orthodontic tooth movement. Keywords: Anterior alveolus, High angle, Low angle, Lateral cephalometric radiograph, Saudi individuals